Investigate transformation characteristic of shape memory alloys - Yeo, Wei Jie (2012)
In recent years, being a smart material, shape memory alloys also known as SMA have increasingly shown great prospect in applications of engineering, control, medicine and machine with its memory function, favorable super-elasticity (SE), physio-chemical performance and biocompatibility. Due to the interesting and unique properties of SMA, the author would like to investigate the transformation characteristic, in this case, it would be the Nickel-Titanium wire also known as Nitinol wire.